INTEGRASI MEDIA SOSIAL UNTUK MENINGKATKAN PEMBELAJARAN ANTAR SISWA PADA PEMBELAJARAN PAI - Nuratika; Decky Saputra (EL-TA’DIB: Journal of Islamic Education, 2025)
The integration of social media into Islamic Religious Education (PAI) learning represents a form of pedagogical adaptation to the development of 21st-century digital technology. Social media function not only as communication tools but also as platforms for collaborative learning among students that support the deep learning approach and the principles of the Merdeka Curriculum. This study aims to examine how social media such as WhatsApp, Telegram, and Instagram are utilized to build reflective interaction, strengthen metacognition, and foster students’ critical thinking skills within the context of PAI learning. This research employs a qualitative approach with a descriptive-analytical method through observations of social media–based learning activities among senior high school students. The findings indicate that well-directed use of social media can enhance spiritual communication, broaden learning engagement, and cultivate collaboration and empathy among students. Therefore, the integration of social media can function as a learning ecosystem that enriches the practice of Islamic education in the digital era. Keywords: Social Media, Peer Learning, Islamic Religious Education (PAI), Deep Learning, Merdeka Curriculum